Towards responsible resource utilization: A review of sustainable vs. unsustainable reuse of wood waste. - Eric Agyemang; Kwadwo Ofori-Dua; Peter Dwumah; John Boulard Forkuor (PLoS ONE)
Abundant wood waste is generated globally, but the literature lacks a framework distinguishing sustainable versus unsustainable reuse practices. This gap hinders policy makers and stakeholders from effectively supporting responsible resource utilization. As such, this scoping review aimed to address this gap by evaluating wood waste reuse practices through ecological, financial, and social sustainability lenses. A comprehensive database search yielded 1,150 records, narrowed to 106 included studies through eligibility screening. Data on study details and sustainability factors was extracted without a formal quality appraisal. The protocol ensures a rigorous evidence-mapping approach. The findings revealed that sustainable uses included renewable energy, adsorbents, construction materials, and composting applications. However, toxic preservatives, uncontrolled emissions from burning, intensive harvesting impacts, and contamination risks from uncontrolled mulching perpetuate ecological, social, and financial challenges. Preventing contamination and managing sustainability trade-offs are key priorities. Research innovations, stringent quality control, and supportive policies are imperative to distinguish practices aligned with sustainability principles from those inadvertently causing harm. This review provides a comprehensive framework for making informed decisions to progress wood waste systems toward responsible resource utilization.